Selected Aspects of the Road Traffic Safety Management System - Monika Stoma; Jacek Caban; Agnieszka Dudziak; Andrzej Kuranc (Communications - Scientific letters of the University of Zilina, 2021)
The article is an attempt to present the two modern concepts of safety management systems. The first is the sunflower pyramid used especially in Europe, the second is the ISO 39001 standard (Road Safety Management System) of international scope. The idea and possibilities offered by use of both concepts of safety management, as well as an attempt to assess the impact of their actions on decrease in fatalities in selected EU countries, were presented. As a result of the conducted analyses, a downward trend was noted as to the number of certificates issued for compliance with the ISO 39001 standard in the world, which may indicate an appearance of the more adequate management systems, or other tools or concepts to improve the road safety, or inadequate education society and low level of awareness in this area of stakeholders, including politicians, scientists, producers, drivers (professional and reliable), as well as other road users, including unprotected ones.